Peran Penyuluh dalam Meningkatkan Motivasi Petani pada Usahatani Tanaman Lada di Desa Bisikori Kecamatan Moramo - Salsa Aulia; Musadar Mapasomba; Salahuddin salahuddin (Jurnal Ilmiah Penyuluhan dan Pengembangan Masyarakat, 2021)
This study aims to (1) determine the role of extension workers in increasing the motivation of farmers in pepper farming, (2) find out how the motivation of farmers in pepper farming. (3) How is the relationship between the role of agricultural extension workers and the level of motivation of farmers in pepper farming in Bisikori Village, Moramo District. The sample in this study was determined by simple random sampling. Analysis of the data used in this study is a descriptive method which is processed using the Sperman Rank Correlation formula. The results of this study indicate that (1) The role of extension workers in Bisikori Village, Moramo District is still less active, extension services have not carried out all tasks or indicators of the role of agricultural extension workers optimally, so that the farming community has not fully felt the role of PPL. (2) The level of motivation of farmers in farming pepper plants in Bisikori Village, Moramo District is in the low category, this is due to pests and diseases that have not been resolved until now, the role of agricultural extension workers who are not active and the price of pepper plants is decreasing every year. (3) The role of agricultural extension workers is significantly related to the motivation level of pepper plants. The results showed that the role of agricultural extension workers was significantly related to the motivation level of pepper farmers in Bisikori Village, Moramo District, South Konawe Regency. Extension workers who are not active will affect the level of motivation of farmers in farming, feel that they really need the presence of agricultural fans to support their farming activities.